2021
DOI: 10.1038/s41746-021-00423-6
|View full text |Cite
|
Sign up to set email alerts
|

The potential of artificial intelligence to improve patient safety: a scoping review

Abstract: Artificial intelligence (AI) represents a valuable tool that could be used to improve the safety of care. Major adverse events in healthcare include: healthcare-associated infections, adverse drug events, venous thromboembolism, surgical complications, pressure ulcers, falls, decompensation, and diagnostic errors. The objective of this scoping review was to summarize the relevant literature and evaluate the potential of AI to improve patient safety in these eight harm domains. A structured search was used to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 66 publications
0
78
0
2
Order By: Relevance
“…The authors found that such complications reduce patient satisfaction, incur cost, and worsen outcomes for patients [ 139 , 140 ]. Brain tumour surgery may also benefit from greater AI integration by helping to predict and mitigate the development of numerous other typical post-operative complications, including adverse drug events [ 141 ], venous thromboembolism [ 142 ], development of pressure ulcers [ 143 , 144 ], falls [ 145 ], and hypoglycaemia [ 146 , 147 ]. These complications are all-too-often preventable, and significantly affect patient outcomes.…”
Section: Post-operative Phasementioning
confidence: 99%
“…The authors found that such complications reduce patient satisfaction, incur cost, and worsen outcomes for patients [ 139 , 140 ]. Brain tumour surgery may also benefit from greater AI integration by helping to predict and mitigate the development of numerous other typical post-operative complications, including adverse drug events [ 141 ], venous thromboembolism [ 142 ], development of pressure ulcers [ 143 , 144 ], falls [ 145 ], and hypoglycaemia [ 146 , 147 ]. These complications are all-too-often preventable, and significantly affect patient outcomes.…”
Section: Post-operative Phasementioning
confidence: 99%
“…IBM Watson is an example of an AI-based system used in healthcare for various use also in clinical trials [37]. As phase IV clinical trial is very beneficial for safety, effectiveness, and post approval assessments also Known as Postmarketing surveillance (PMS) [36] AI can improve patient safety including ADR monitoring [38]. VigiRank, VigiMatch are examples of AIbased databases for PV [35].…”
Section: Clinical Trialmentioning
confidence: 99%
“…Nonknowledge-based systems require a sufficient data source in order to use machine learning and statistical pattern recognition, which currently drive a strong artificial intelligence movement, to develop recommendations [4-6]. These algorithms have the great advantage that, as learning systems, they can improve their recommendations as the volume of data increases.…”
Section: Available Systems: Knowledge Based Versus Ai/machine Learning Basedmentioning
confidence: 99%
“…However, the correct dosage of the corresponding (alternative) medication also harbors considerable sources of error. Bates et al [6, 43] found that almost a third of the ADEs were in principle preventable [44].…”
Section: Minimizing Medication Errorsmentioning
confidence: 99%